Recovery of Photosynthesis in Sunflower after a Period of Low Leaf Water Potential - Boyer, J. S. (1971)
Photosynthesis was studied in sunflower plants subjected to 1 to 2 days of desiccation and then permitted to recover. The leaf water potential to which leaves returned after rewatering was dependent on the severity of desiccation and the evaporative conditions. Under moderately evaporative conditions, leaf water potential returned to predesiccation levels after 3 to 5 hours when desiccation was slight. Leaf water potentials remained below predesiccation levels for several days after rewatering when leaf water potentials decreased to −13 to −19 bars during desiccation. Leaf water potential showed no sign of recovery when leaf water potentials decreased to −20 bars or below during desiccation. The lack of full recovery of leaf water potential was attributable to increased resistance to water transport in the roots and stem. The resistance ultimately became large enough to result in death of the leaves because net water loss continued even after the soil had been rewatered. Measurements of photosynthesis were made at high light intensities, where stomatal aperture often affects photosynthesis, and at low light intensities, where the photochemical activity of the leaves limits photosynthesis. Providing leaf water potentials remained above −12 bars during the desiccation period and returned to predesiccation levels during recovery, photosynthesis under both low and high light paralleled the recovery in leaf water potential after rewatering. After desiccation to leaf water potentials below −12 bars, recovery was incomplete under high light and could be attributed to lack of full stomatal opening. Lack of full opening persisted for 3 days and showed no sign of eventual recovery even though leaf water potentials recovered fully. Under low light, however, recovery in photochemical activity was complete within 15 hours after desiccation to leaf water potentials as low as −17 bars.